COMMON METHODS OF EXAMINATION OF NORMATIVE LEGAL ACTS ON THE BASIS OF EXPERIENCE OF THE EUROPEAN UNION - Zhamaladen Ibrahimovic Ибрагимов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article states about the basic characteristics, general principles of the examine and organization of legal expertise, its consolidation as the main form of relationship between the public sector and the government. Authors based on the international experience reveal different organizational and methodological aspects of the examine